Evaluation of the impact of International standards set by "The Basle Committee on Banking Supervision" on Jordanian law - Al-Anani, Nadia A. (Durham Law School, Durham University, 2009)
Formulating international standards on banking supervision is one of the most important topics of international financial law. The recent international financial crisis is another striking example on the significance and relevance of this subject. This thesis attempts to evaluate the impact of international standards of banking supervision aimed at the creation of a "safe and sound" banking system on Jordanian legislation at two levels: to what extent international standards set out by the Basel Committee on Banking Supervision ("BCBS") have influenced Jordanian law; and how these standards can assist in improving the Jordanian law as well as direct new policy reforms. The first finding of the thesis is that Jordanian law is significantly compliant with international standards. The second main finding is that soft law, as opposed to hard law, is the optimal form of setting international banking supervisory standards. The thesis also finds that the BCBS standards do not provide adequate guidance on the structure of the banking supervisory authority. The thesis concludes with recommendations on how to enhance international banking supervisory standards as well as the structure and substantive law of banking supervision in Jordan in light of international standards and with occasional reference to the UK Law.